Searching evidence for climatic change: Analysis of hydro-meteorological time series in the Upper Indus Basin - Khan, A.R. (International Water Management Institute, 2001)
The study examines some of the major components of water cycle in the Upper Indus Basin (UIB) to look for evidence of climate change. An analysis of hydrometeorological data has been performed for UIB. An Additive Decomposition Model was used for analyzing the time series data from ten meteorological stations in the Mangla (Jhelum River) and the Tarbela (Indus River) catchments and the long-term flow data for the three major rivers, the Indus, Jhelum and Chenab. The model decomposes a time series into trend, cyclical or periodic, autoregressive and irregular components. Furthermore, spectral analysis is done in order to display these components of the time series and examine the results of the removal of the components. This approach makes use of the fact that a change in climate, if it has occurred, will have a magnified effect on hydrologic time series. By detecting trends in such series, it should be possible to work backwards and identify the causative climatic change. In case of flow data for the three rivers, which was available for a longer period than the meteorological data, the ?F? and ?t? tests for stability of variance and mean, respectively, were also performed. The annual cycle dominated all the temperature series i.e., large periodic components, and none explained by the periodic component and a dominant random component. In case of stream- flow data, the annual temperature cycle was dominant and no trend components were found in any of the flow series. The F-test and the t-test indicated the variances and means for different sub- periods of each flow series to be stable at 5% level of significance. The analysis of time series of river flows and associated climatic data did not find any pattern of trends likely to be caused by ?greenhouse warming? in the Upper Indus Basin.